2019
DOI: 10.18502/jder.v2i1.566
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Disaster Management Training Program on Knowledge, Attitude, and Practice of Hospital Staffs in Natural Disasters

Abstract: Introduction: Hospitals have a very important role in responding to disasters. Since nurses are one of the largest group of the health team and play multi-roles in patient treatment, improvement of their knowledge and skills helps them to act better in disasters.The purpose of this study was to investigate the effect of a disaster management training program on the level of knowledge, attitude, and practice of nursing staffs. Methods: The present interventional study was conducted in Shahid Rahnemoon Hos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
21
1
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(27 citation statements)
references
References 0 publications
4
21
1
1
Order By: Relevance
“…Applying various other teaching methods combined with lecturing can promote the level of nurses' preparedness; therefore, we can use such combined methods to improve the efficacy of education. Lecturing is a common procedure used to increase knowledge; other studies have also confirmed its efficacy, approving our findings [9,11]. Using handbooks for nurses has successfully enabled them to achieve considerable awareness in coping with disasters and modifying their attitudes [10].…”
Section: Discussionsupporting
confidence: 68%
See 2 more Smart Citations
“…Applying various other teaching methods combined with lecturing can promote the level of nurses' preparedness; therefore, we can use such combined methods to improve the efficacy of education. Lecturing is a common procedure used to increase knowledge; other studies have also confirmed its efficacy, approving our findings [9,11]. Using handbooks for nurses has successfully enabled them to achieve considerable awareness in coping with disasters and modifying their attitudes [10].…”
Section: Discussionsupporting
confidence: 68%
“…Therefore, the increased preparedness of healthcare systems for identifying risks and responding appropriately to disasters is of utmost importance [8]. Preparedness of hospitals against natural disasters influences their performance in the best care provision and increases their capacity for suitable responding in these conditions [9]. The global reports stated that the approval of plans and policies, designing and building resilient hospitals at the national level, assessment of hospital safety, education, protection of personnel and equipment, and strategic planning for emergency responding are among the facilities and approaches for safe care provision [8].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some studies reported that nurses' awareness of their role and skills in disasters was not adequate, they were not well prepared for future disasters (Basnet, Songwathana, & Sae-Sia, 2016;Yan, Turale, Stone, & Petrini, 2015), this was because they did not have enough training for disaster preparedness, but that the training programs carried out on this area positively affected nurses' preparedness to respond to disasters (Ghanbari, Maddah, Khankeh, & Karimloo, 2011;Mirzaei, Adel, Sadeghian, Kazemi, & Nadjarzadeh, 2019). In another study, the training was shown to make nurses more prepared to respond to disasters (Goodhue et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…31 Although gray literature is not formally published in the same way as traditional academic literature, such as books, journal, and conference articles, it includes academic theses, organization reports, government papers among others which may prove to be highly influential in research and systematic reviews. 32 In the context of this study, gray literature plays an important role as it enables the researchers to gather useful data for a study. The analysis, including selection and inclusion procedures, are discussed in Section 3.2.1 (Figure 2).…”
Section: Literature Search Strategymentioning
confidence: 99%